PERANAN CONTROLLER DALAM PERENCANAAN DAN PENGENDALIAN PENJUALAN PADA PT DUTA MULTI KARYA BATAM - Hendry Jaya (Universitas Riau Kepulauan, 2016)
This study aims to determine the role of the controller in the planning and control of sales at PT Duta Multi Karya. The data used to know issues under discussion and namely qualitative data, while based on sources using primary data and secondary data. The method used in this research is descriptive method. Which aims to provide a clear picture about the object of research . The results showed that the planning of sales at PT Duta Multi Karya with has been running well, where the existing system of internal controls within the company.In this case the Company Duta Multi Karya do a controller for controlling the sales and financial The method used the company Duta Multi Karya is using discounts.Keywords: The role of Controller, Plan, Sales Control